2006
DOI: 10.1203/01.pdr.0000203104.45807.23
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Recurrent Hypoxia in Developing Rat Attenuates Respiratory Responses to Subsequent Acute Hypoxia

Abstract: Whereas definitive treatment of pediatric conditions associated with hypoxemia reverses many pathologic symptoms, some physiologic dysfunctions appear to persist. These abnormalities are attributed to long-lasting central effects of prior hypoxia. To investigate such effects in an animal model, male rats were exposed to FiO 2 ϭ 0.12 continuously for 7 h daily from postnatal day (p) 17 (representing early childhood) through p33 (representing adolescence), defined as recurrent hypoxia. Respiratory responses duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Parameters were frequency of breathing (f R ); tidal volume (V T ); ventilation (V̇); inspiratory time (T I ); expiratory time (T E ); V T /T I , an index of respiratory drive (Moss et al, 2006); peak inspiratory flow (PIF), and peak expiratory flow (PEF). The provided software constantly corrected digitized values for changes in chamber temperature and humidity.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Parameters were frequency of breathing (f R ); tidal volume (V T ); ventilation (V̇); inspiratory time (T I ); expiratory time (T E ); V T /T I , an index of respiratory drive (Moss et al, 2006); peak inspiratory flow (PIF), and peak expiratory flow (PEF). The provided software constantly corrected digitized values for changes in chamber temperature and humidity.…”
Section: Methodsmentioning
confidence: 99%
“…This short-term facilitation (STF), which occurs in humans (Dahan et al, 1995), rats (Moss et al, 2006), and mice (Kline and Prabhakar, 2001; Kline et al, 2002), is due to a central neural mechanism that drives ventilation independently of peripheral or central chemoreceptor inputs (Millhorn et al, 1980). Although little is known about the underlying neurochemical processes, STF is markedly diminished in nNOS knock-out mice (Kline and Prabhakar, 2001; Kline et al, 2002), suggesting a role for excitatory SNOs rather than NO per se .…”
Section: Introductionmentioning
confidence: 99%
“…Provided software constantly corrected digitized values for changes in chamber temperature and humidity and a rejection algorithm excluded motion-induced artifacts. Due to the minor differences in body weights between the males and females, parameters such as V T , PIF and PEF, often corrected for body weight (Moss et al, 2006) are presented without corrections.…”
Section: Methodsmentioning
confidence: 99%
“…Cessation of exposure to hypoxia often results in ventilatory parameters increasing or remaining above baseline for a substantial period of time. This “short-term facilitation (STF)” of ventilation, first detailed in anesthetized cats (Wagner and Eldridge, 1991), also occurs in awake or sleeping humans (Dahan et al, 1995) and rats (Moss et al, 2006), and is activated by a central neural mechanism with slow dynamics that drives ventilation independently of peripheral or central chemoreceptor inputs (Millhorn et al, 1980). …”
Section: Introductionmentioning
confidence: 99%
“…However, the neural structures, neurotransmitters, and downstream signaling pathways underlying such biphasic changes in HVR induced by IH are unknown. Using an immature rat model simulating OSA, Moss et al investigated effects of chronic IH (12% O 2 , 7 h daily) on rats from postnatal day 17 (representing early childhood) through day 33 (representing adolescence) and day 47 (adult) ( 55 ). They reported that chronic IH produced long-lasting attenuation in respiratory responsiveness to subsequent acute hypoxia.…”
Section: Effects Of Chronic Intermittent Hypoxia On Development In Nementioning
confidence: 99%